2021
DOI: 10.1186/s13195-021-00846-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity and metacognition in persons with subjective cognitive decline (COSCODE): rationale and study design

Abstract: Background Subjective cognitive decline (SCD) is the subjective perception of a decline in memory and/or other cognitive functions in the absence of objective evidence. Some SCD individuals however may suffer from very early stages of neurodegenerative diseases (such as Alzheimer’s disease, AD), minor psychiatric conditions, neurological, and/or somatic comorbidities. Even if a theoretical framework has been established, the etiology of SCD remains far from elucidated. Clinical observations rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Furthermore, the risk of progression to dementia is substantially increased in case of the presence of amyloid deposition (ie, a hazard ratio of 17.0 compared with SCD with normal AD biomarkers). For these reasons, individuals with SCD are increasingly targeted in research and prevention initiatives, and are frequently included in research studies involving amyloid-PET (eg, ABIDE, AMYPAD-DPMS, DELCODE, SCIENCe, COSCODE, ALFA+). Previous studies have shown that amyloid-PET has substantial clinical consequences in terms of diagnostic change and improvement of diagnostic confidence in SCD, and many of these individuals are proactively seeking medical advice and information about their amyloid status …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of progression to dementia is substantially increased in case of the presence of amyloid deposition (ie, a hazard ratio of 17.0 compared with SCD with normal AD biomarkers). For these reasons, individuals with SCD are increasingly targeted in research and prevention initiatives, and are frequently included in research studies involving amyloid-PET (eg, ABIDE, AMYPAD-DPMS, DELCODE, SCIENCe, COSCODE, ALFA+). Previous studies have shown that amyloid-PET has substantial clinical consequences in terms of diagnostic change and improvement of diagnostic confidence in SCD, and many of these individuals are proactively seeking medical advice and information about their amyloid status …”
Section: Introductionmentioning
confidence: 99%
“…Table 1). In line with 76 , SCD was defined based on the following criteria: persons asking for help and consulting to the GMC for self-experience of deterioration in cognitive abilities, without objective cognitive impairment detected through formal neuropsychological testing. MCI was defined based on the following clinical criteria: (i) objective evidence of cognitive impairment, (ii) cognitive concern reported by the patient and/or informant (family or close friend), and (iii) little or no functional impairment in daily living activities 51 .…”
Section: Methodsmentioning
confidence: 99%
“…The individuals were classi ed as SCD if they reported cognitive complaints to the physician, without objective evidence of impairment. [19] The diagnostic workup includes clinical, neurological, and neuropsychological assessments as well as an MRI scan. Thanks to several interconnected ongoing research studies, some patients also undergo amyloid, tau PET scans, APOE genotyping, and blood-based biomarkers assessment.…”
Section: Populationmentioning
confidence: 99%
“…Thanks to several interconnected ongoing research studies, some patients also undergo amyloid, tau PET scans, APOE genotyping, and blood-based biomarkers assessment. [19] The neuropsychological battery assessed global cognition (Mini-Mental State Examination, MMSE), memory (3 objects 3 places; Free and Cued Selective Reminding Test delayed recall, FCSRT; digit span), language (category and phonemic uency), attention (Trial Making Test, TMT, A, digit symbol forward), executive functions (TMT B, TMT B-A, digit symbol backward), and visuospatial abilities (Clock). Anxiety and depression were also assessed (Hospital Anxiety and Depression Scale, HADS).…”
Section: Populationmentioning
confidence: 99%